Hubungan Self-Efficacy Terhadap Kualitas Hidup Pasien Kanker Serviks Di RSUD Dr. Moewardi - Sindi Lutfiana Dariska; Rinda Intan Sari; Diffa Risqa Arisdiani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Cervical cancer is a type of deadly malignant cancer that attacks women. So that it can affect the quality of life for sufferers and Self Efficacy is needed. Purpose: Knowing the relationship of self-efficacy to the quality of life of cervical cancer patients. Research method: Quantitative research design with a sample of 50 respondents, the technique used is purposive sampling. Results: Based on age, education, and length of illness, bivariate results obtained using the sperman rank correlation test showed that the p-value was 0.002 (<0.05) meaning that there was a significant relationship between self-efficacy and the quality of life of cervical cancer patients. The correlation coefficient value obtained was 0.429, meaning that the relationship between self-efficacy and the quality of life of cervical cancer patients showed a moderate relationship with a positive direction, meaning that the higher the self-efficacy, the better the quality of life of cervical cancer patients. Suggestion: Future researchers can focus on one respondent who is undergoing chemotherapy or who is currently on an outpatient basis.